Konsep dan Sistem Nilai Dalam Ajaran Agama Islam dan Aliran-Alirannya - Nurliana Damanik (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2022)
Value is an abstract reality, value may be felt in each person as a driving force or principles that guide life. Values can also manifest out in patterns of behavior, attitudes and mindsets. Value in Arabic itself is not non-material or abstract. Values that are not visible but real can be seen seeing the benefits. Value comes from the root word qiimatun from which the word qoyymatuun is also formed which means straight, as in QS. Al-Bayyinah:3-5. Values and virtues in Islam have two aspects, namely normative and operative aspects. Which includes good grades, half good grades, neutral grades, poor grades, and bad grades. The main values of Islamic teachings have aqidah values, sharia values, and moral values.